Effect of Indurance Training Techniques on the Vo2 Max Increases of the Gergo Roman Wrestling Athletes in the Gold-for-Indonesia Program in the Sea Games XXVII Myanmar 2013 - Hadi, Rubianto; Setijono, Hari; Soegiyanto, Soegiyanto; Rahayu, Setyo (The Journal of Educational Development, 2018)
The Sport of Wrestling is rarely heard in Indonesia but the real fact is not so. Although it is not as popular as football, badminton, or tennis, this type of hard sport still exists in Indonesia. The purpose of this study is to determine whether interval of the endurance training techniques with the training program software can improve the VO2 Max of the wrestling athletes in the Gold-for-Indonesia Program in the Sea Games XXVII Myanmar 2013. The method used in this research was the experimental method; the researchers deliberately and systematically incorporated treatments into natural phenomena and then observed the its effects. The results show that, overall, the VO2 Max of the pretest result is 46.95%, the result of the first cycle test shows an increase to 49.43%, and the second cycle test shows even better result to 50.21%. To improve the endurance of the wrestling athletes of the program of Gold-for-Indonesia in the Sea Games XXVII Myanmar 2013, the trainers need to use the interval of endurance training techniques with the software of the training program.